ANALISIS DETERMINAN KECENDERUNGAN KECURANGAN AKUNTANSI DI SEKTOR PUBLIK - Avilia Yussy Primadhany; Abriyani Puspaningsih (Behavioral Accounting Journal, 2018)
The purpose of this research is to determine the effect of effectiveness of internal control systems, compensation systems, and leadership styles to accounting fraud tendencies in Government sectors. The sampling technique used purposive sampling. Data was collected through questionnaire that given directly to officers from accounting or financing department including heads of financial sub section in Sukoharjo Government office. The data obtained were analyzed by using Statistical Package for Social Sciences (SPSS). The results showed that (1) effectiveness of internal control systems had a negative significant affect to accounting fraud tendencies, (2) compensation systems had not significantly but possitive affect to accounting fraud tendencies, and (3) leadership styles had not significantly but negative affect to accounting fraud tendencies.